Role of Galectin-9 in Atopic Dermatitis — Is It Mediated Through E Selectin? A Clinical and Immunohistochemical Study - Farag AGA; Al-Sharaky DR; Allam SS; Khaled HN (Dove Medical Press, 2020)
Azza Gaber Antar Farag, 1 Dalia Rifaat Al-Sharaky, 2 Sawsan Samy Allam, 3 Hesham Nabil Khaled 1 1Dermatology, Andrology and STDs Department, Faculty of Medicine, Menoufia University, Shebin ElKom, Egypt; 2Pathology Department, Faculty of Medicine, Menoufia University, Shebin ElKom, Egypt; 3Dermatology, Ministry of Health, Damanhour, Behera, EgyptCorrespondence: Azza Gaber Antar FaragDermatology, Andrology and STDs, Faculty of Medicine, Menoufia University, Shebin ElKoom, Al Menoufia 32511 EgyptTel +201097787204Fax +20 248 2226454Email azzagaber92@yahoo.comBackground: Atopic dermatitis (AD) is a recognized T helper (Th)2, allergic, skin disease. Galectin-9 (gal-9) is a member of galectin family. It alters T-cell balance resulting in Th2 polarization. These Th2 cells yield various cytokines that may influence E selectin expression. Therefore, we hypothesized that gal-9 may have an active role in AD and this role could be mediated through E selectin.Objective: To assess this hypothesis, immunohistochemical expression of gal-9 and E selectin was investigated in skin lesions, from atopic dermatitis patients, and compared.Methods: Twenty-two atopic dermatitis patients and ten controls were included in this case-control study. SCORAD score was used to evaluate atopic dermatitis severity. Biopsies from skin lesions of AD patients and matched sites of controls were taken and stained immunohistochemically by gal-9 and E selectin polyclonal antibodies.Results: Compared to controls, atopic dermatitis patients exhibited a significant increased gal-9 H score, percent of expression, cellular localization (P˂0.001) and intensity (P=0.04) as well as dermal cellular infiltrate (P˂0.001). Also, there were significant elevations in E selectin H score (P=0.002), percent of expression (P=0.001) and cellular localization (P< 0.001) as well as dermal inflammatory infiltrates in AD cases than controls. In AD, 20 cases showed co expression of both gal-9 and E selectin in the epidermis with insignificant correlation between their H scores.Study Limitations: This study only included a small number of studied subjects.Conclusion: Galectin-9 and E selectin participates independently in atopic dermatitis pathogenesis, that may help in development of new therapeutic agents in atopic dermatitis management program.Keywords: galectins, E- selectin, atopic dermatitis